Reconstruction of Examination of Marriage Dispensation As a Effort to Protect Children - Nugraha, Alfajar (Lembaga Penelitian dan Pengabdian kepada Masyarakat, UIN Sultan Aji Muhammad Idris Samarinda, 2023)
Abstract Marriage dispensation is one of the problems that is still unfinished to be discussed where there is a lot of debate that the marriage dispensation is a legality of underage marriage on the grounds that the provision of marriage dispensation is not based on child protection even some decisions of the Religious Courts have become a material for criticism where the consideration of the judges' decisions is still considered